Tax Planning Activities and Firm Value (Study In Indonesia Consumer Goods Companies Listed in IDX Period 2016 to 2020) - Farid Muhammad Kifli; Agung Juliarto (Diponegoro Journal of Accounting, 2022)
The objective of this research is to examine the effect of tax planning measured by using three proxies (tax per share, effective tax rate, and book-tax differences per share) on the firm value. The study's total sample was 27 companies in Consumer Goods sector listed on Indonesia Stock Exchange between 2016 to 2020, with total of 135 observation.  The sample was selected using purposive sampling method and the analysis technique used panel data regression with the Eviews-10 application. The findings of this study reveal that: Model 1 that using tax per share has a positive and significant effect on firm value which suggests that tax planning has a negative impact on firm value. Model 2 that using effective tax rate has no significant effect on firm value which indicates that no influence of tax planning on firm value. Model 3 that using book-tax differences per share has a positive influence on firm value which means that tax planning positively affects firm value.